On the emergence of Criminology and Criminalistics in Vienna of the first republic - Kamila Staudigl-Ciechowitz (Journal on European History of Law)
This article focuses on criminalistics and criminology in Austria, with a particular emphasis on Vienna during the interwar period. Drawing from largely unpublished source material, it describes the founding of the University Institute for Comprehensive Criminal Law and Criminalistics and examines the individuals involved and the content of the courses offered. Special attention is given to Wenzel Gleispach as the founder of the institute and its scientific staff. In this context, the question of the Faculty of Law opening its doors to women as employees is explored. This institute was the first within the Faculty of Law and Political Science to hire women as academic staff. Finally, the article explains the relationship between the institute and the Criminological Institute of the Vienna Police Directorate.